1999
DOI: 10.1038/sj.onc.1202901
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of protein kinase (Krs/MST) activation for MT-21-induced apoptosis

Abstract: Fas is a well characterized apoptosis-inducing factor. One of our synthetic compounds, MT-21, induced apoptosis in human leukemia HL-60 cells similar to Fas. MT-21 activated caspase-3, an important cysteine aspartic protease for apoptosis induction. MT-21 also activated c-Jun-NH 2 -terminal kinase (JNK), a member of mitogen activated protein kinase (MAPK) superfamily that is involved in the regulation of cell growth, di erentiation and cell death. Moreover, MT-21 treatment resulted in the activation of a 36 kD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 43 publications
3
51
0
Order By: Relevance
“…Ectopic expression of MST induces apoptosis, and a kinase-dead mutant in HL-60 cells inhibits both JNK activation and apoptosis. 57 Similar results are obtained when BJAB or 293T cells are used. The physiologic targets of activated MST are unknown, although transfection of 293T cells with MST1 activates MKK7, MKK6, SAPK, and p38 MAPK.…”
Section: (V) Stress Management During Cell Deathsupporting
confidence: 74%
“…Ectopic expression of MST induces apoptosis, and a kinase-dead mutant in HL-60 cells inhibits both JNK activation and apoptosis. 57 Similar results are obtained when BJAB or 293T cells are used. The physiologic targets of activated MST are unknown, although transfection of 293T cells with MST1 activates MKK7, MKK6, SAPK, and p38 MAPK.…”
Section: (V) Stress Management During Cell Deathsupporting
confidence: 74%
“…Camptothecin, etoposide, mitomycin C, doxorubicin, bleomycin, staurosporine, actinomycin D, colcemid, taxol, and 5-fluorouracil were purchased from Wako Pure Chemicals, Ltd. (Osaka, Japan). Cloning of human fulllength MST/krs1 and MST/krs2 cDNA and constructions of expression vectors of kinase-inactive MST/krs1 and MST/krs2 were performed as described previously (17).…”
Section: Methodsmentioning
confidence: 99%
“…It is possible that most apoptotic signals including the Fas-mediated signal and the cytotrienin-induced signal activate several pathways for apoptosis in a target cell. Unlike these apoptosis inducers, MT-21 (3-acetyl-4,5-dimethyl-5-octyloxy-3-pyrrolin-2-one), our synthetic apoptosis inducer, activates the signal from caspase-3, MST/Krs to JNK in a rather simple manner (16,17). In the present study, we have investigated the caspase-mediated proteolytic activation of MST/Krs proteins in cytotrienin A-sensitive and -resistant human tumor cell lines.…”
mentioning
confidence: 99%
“…The stimuli reported to induce JNK-dependent cell death are stress inducers such as UV-and g-irradiation (Chen et al, 1996;Zanke et al, 1996;Butterfield et al, 1997;Tournier et al, 2000) as well as cytotoxic drugs (Chen et al, 1999;Shiah et al, 1999Shiah et al, , 2001Watabe et al, 1999;Eichhorst et al, 2000;Mandlekar et al, 2000;SanchezPerez et al, 2000;Wang et al, 2000) and anticarcinogenic compounds such as isothiocyanates (Chen et al, 1998). Thus, JNK has been suggested to be required for stress-induced mitochondrial death signaling pathways (Tournier et al, 2000).…”
Section: Role Of Jnk In Ajoene-induced Apoptotic Signalingmentioning
confidence: 99%
“…Activation of mitogen-activated protein kinases (MAPKs) is considered to be a pivotal step in ROS-induced signaling pathways. In fact, it has been shown that increased ROS production in leukemic cells leads to the activation of MAPKs and cell death (Chen et al, 1998;Shiah et al, 1999;Watabe et al, 1999;Zhuang et al, 2000).…”
Section: Introductionmentioning
confidence: 99%